2005
DOI: 10.1107/s0021889805005029
|View full text |Cite
|
Sign up to set email alerts
|

Sample size: an important parameter in flash-cooling macromolecular crystallization solutions

Abstract: The effect of sample size on flash-cooling was assessed using an assortment of Hampton Screen I solutions (Hampton Research). These were cryogenically cooled to ascertain the minimum glycerol concentration needed for vitrification of solutions. Solutions were 'flash-cooled' in 1.0, 0.5 and 0.1 mm commercial cryoloops, using a 100 K nitrogen stream generated by an Oxford 600 Cryostream. The loops were visually examined and then X-ray diffraction data were collected and evaluated for ice formation. The glycerol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 25 publications
2
44
1
Order By: Relevance
“…2. These contraction values, in combination with other recent results (Chinte et al, 2005;Geremia et al, 2006;Berejnov et al, 2006), offer new methods of approaching the cryocooling problem.…”
Section: Figurementioning
confidence: 60%
See 1 more Smart Citation
“…2. These contraction values, in combination with other recent results (Chinte et al, 2005;Geremia et al, 2006;Berejnov et al, 2006), offer new methods of approaching the cryocooling problem.…”
Section: Figurementioning
confidence: 60%
“…The external cryosolution need not contain penetrating cryoprotective agents, but should prevent ice formation. Critical concentrations for ice prevention in crystal-sized samples of various solutions have been reported (Garman & Mitchell, 1996;McFerrin & Snell, 2002;Chinte et al, 2005;Berejnov et al, 2006). Thus, if the internal cryosolution is above this concentration, it will probably be an effective external cryosolution as well.…”
Section: Choosing the Internal Cryosolution: Qualitativementioning
confidence: 99%
“…It is important to notice that the concentration of cryoprotectant required to ensure the formation of an amorphous glass on flash-cooling is a lower limit to what may be appropriate for producing the best diffraction from the cooled crystal (Mitchell & Garman, 1994). Furthermore, recent work by the Schall group has shown that the concentration of cryoprotectant required for a successful amorphous freeze is highly dependent on the size of the crystal (Chinte et al, 2005). For systems that tolerate high levels of cryoprotection poorly, choosing a small crystal may solve the problem.…”
Section: Cryoprotectionmentioning
confidence: 99%
“…The moderate viscosity of the novel oil-based cryoprotectant containing paraffin oil is lower than that of 100% Paratone-N, which improves the visibility of the mounted crystal in the cryoloop and is advantageous for removing the excess cryoprotectant solution from the loop. The smaller sample size was reported to be helpful for successful flash-cooling of protein crystals in terms of cooling rate (Chinte et al, 2005), suggesting another advantage of reducing the protectant volume surrounding the crystal. The dry paraffin oil (Riboldi-Tunnicliffe & Hilgenfeld, 1999) may be also effective as an oil-based versatile cryoprotectant, although it cannot be applied to the heavy-atom derivatization of protein crystals.…”
Section: Discussionmentioning
confidence: 99%